ARE ONLINE COURSES CANNIBALIZING STUDENTS FROM EXISTING COURSES? - Cavanaugh, Joseph K. (Online Learning, 2005)
One of the reasons most often cited for the increasing number and popularity of online courses is the format’s ability to provide access to students who cannot attend conventionally delivered face-to-face courses. Are these underserved students in fact the ones enrolling in online courses? Or are online course enrollees the same students who would otherwise be taking face-to-face courses? This analysis uses student registration information from six different online courses at two campuses of a Midwestern university to investigate how students taking online courses compare to the entire student population. In particular, this study addresses whether or not students take online courses to eliminate significant commuting time when they are located long distances from campus.